(untitled) - Garavuso, Vicki; Vicki Garavuso (Boston)
In response to concerns about teacher retention, especially among teachers in their first to fourth year in the classroom, we offer future teachers a series of brief guides full of practical advice that they can refer to in both their student teaching and in their first years on the job
Includes bibliographical references (p. 102-109) and index
Keywords: Mentoring in education; Teachers